Teaching bioinformatics programming in high school: a case report - Costa, Helena Lott; Maia, Giovana C. F.; Chaves, Lucas G. S.; Mariano, Diego; Melo-Minardi, Raquel C. de (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2024)
Bioinformatics requires professionals with knowledge in computing and biological sciences, but teaching it to young people remains a challenge. This article reports on a programming course focused on bioinformatics for high school students. The pilot project, launched in 2024 in Belo Horizonte, Brazil, aimed to integrate programming and Molecular Biology. Using Inquiry-Based Learning (IBL) and gamification, the course engaged students effectively. Activities were divided into quarterly stages, teaching programming through Scratch and projects involving Molecular Biology, such as DNA transcription. The initiative successfully motivated and engaged students in learning Molecular Biology. We hope that the strategies presented here can be adopted by teachers and help inspire a new generation of bioinformaticians.